বাঙালীর জাতীয়তাবাদ - চৌধুরী, সিরাজুল ইসলাম (ঢাকা : দি ইউনিভার্সিটি প্রেস, 2007)
On the political, economic, and social factors that affected the history of nationalism in Bengal from 1830 to 2000.
গ্রন্থপঞ্জিগত নির্দেশিকা (পৃষ্ঠা ৪৪২) ও নির্ঘণ্ট অন্তর্ভুক্ত।
BIED, GenEd
Complimentary copy from BIED, Donated By Akbar Ali Khan, Book Finder International
In Bengali.
Keywords: Nationalism -- India -- Bengal -- History; Bengal (India) -- History